Nitrogen Removal in Permeable Woodchip Filters Affected by Hydraulic Loading Rate and Woodchip Ratio. Issue 5 (1st September 2016) - Bruun, Jacob; Hoffmann, Carl Christian; Kjaergaard, Charlotte
Abstract : Unregulated and event‐driven agricultural tile drainage discharge poses several challenges that potentially limit the nitrate (NO3 ) removal performance of woodchip‐based wetlands constructed to intercept subsurface tile drain flows. Laboratory column tests were conducted to evaluate the biogeochemical response of mixed reactive media (woodchips–seashells and woodchips–Filtralite mixtures) at two woodchip ratios to changes in hydraulic loading rate (HLR). The tests involved continuous loading of aerated artificial drainage water spiked with NO3 –N and tritium ( 3 H2 O) breakthrough experiments. Flow‐normalized NO3 reduction rates ranged from 0.35 to 3.97 g N m −3 L −1, corresponding to N removal efficiencies of 5 to 64%, depending on HLR and filter mixtures. At high HLRs, oxic conditions prevailed in the woodchip filters, resulting in reduced N removal. At low HLRs, progressively lower pore‐water velocities extended the period for consumption of terminal electron acceptors, increasing N removal. When increasing the content of mineral material, N removal declined, probably due to a lower denitrifying biomass at lower woodchip mass. The effect of woodchip ratios on solute transport characteristics was difficult to assess. However, woodchip media including a mineral fraction of crushed seashells demonstrated the highest N removal rates and efficiencies, most likely due to the alkalizing effect of the seashells. In conclusion, filter mixtures consisting of woodchips and seashells were the most effective material for N removal in subsurface flow–constructed wetlands treating agricultural drainage water. Core Ideas: Nonequilibrium solute transport was found in woodchip media. Solute diffusion into immobile zones allowed nitrate removal at high oxygen load. Mixed woodchip media removed 5 to 64% of influent nitrate at continuous loading. Woodchip media including crushed seashells facilitated higher denitrification rates. Increasing the woodchip content in filter media increased treatment efficiency.